Scenarios for the Network Neutrality Arms Race - Lehr, William H.; Gillett, Sharon; Sirbu, Marvin A.; Peha, Jon M. (International Journal of Communication, 2007)
Several factors suggest that meaningful network neutrality rules will not be enshrined in near-term U.S. telecommunications policy. These include disagreements over the need for such rules as well as their definition, efficacy and enforceability. However, as van Schewick (2005)1 has demonstrated in the context of the Internet, network providers may have economic incentives to discriminate in welfare-reducing ways; in addition, network operators may continue to possess market power, particularly with respect to a terminating monopoly.2 On the other hand, the literature on two-sided markets,3 the challenge of cost-recovery in the presence of significant fixed and sunk costs, and the changing nature of Internet traffic all provide efficiency-enhancing rationales for discriminatory pricing and traffic management. Thus, policy-makers face a daunting challenge: discriminatory behavior is likely to occur and distinguishing between good and bad discriminatory behavior is difficult.